Different modes of star formation – II. Gas accretion phase of initially subcritical star-forming clouds. Issue 1 (13th March 2020) - Machida, Masahiro N; Basu, Shantanu
ABSTRACT: The accretion phase of star formation is investigated in magnetically dominated clouds that have an initial subcritical mass-to-flux ratio. We employ non-ideal magnetohydrodynamic simulations that include ambipolar diffusion and ohmic dissipation. During the early prestellar phase, the mass-to-flux ratio rises towards the critical value for collapse, and during this time the angular momentum of the cloud core is reduced significantly by magnetic braking. Once a protostar is formed in the core, the accretion phase is characterized by the presence of a small amount of angular momentum but a large amount of magnetic flux in the near-protostellar environment. The low angular momentum leads to a very small (or even non-existent) disc and weak outflow, while the large magnetic flux can lead to an interchange instability that rapidly removes flux from the central region. The effective magnetic braking in the early collapse phase can even lead to a counterrotating disc and outflow, in which the rotation direction of the disc and outflow is opposite to that of the infalling envelope. The solutions with a counterrotating disc, tiny disc, or non-existent disc (direct collapse) are unique outcomes that are realized in collapse from magnetically dominated clouds with an initial subcritical mass-to-flux ratio.